Annual Bonus Default, Non-Discrimination Principle, and Workers’ Rights Protection in Indonesian Industrial Relations Court - Siti Rahayu; Abas, Muhamad; Rahmatiar, Yuniar (Jurnal Cakrawala Hukum, 2025)
Abstract: Annual bonuses occupy an ambiguous yet legally consequential position in Indonesian employment law: they are neither wages in the strict statutory sense nor purely discretionary employer benefits. This ambiguity generates industrial disputes with significant implications for workers' normative rights. This study examines two central questions: the mechanism for resolving industrial relations disputes under Law Number 2 of 2004 on the Settlement of Industrial Relations Disputes, and the legal analysis of annual bonus default as adjudicated in PHI Decision Number 15/Pdt.Sus-PHI/2024/PN.Bdg. Employing normative legal research through statute and case approaches, this study analyzes primary, secondary, and tertiary legal materials using prescriptive-analytic methodology. The findings reveal that the PPHI Law constructs a mandatory, tiered dispute resolution architecture from bipartite negotiation through mediation, conciliation, and arbitration, to PHI litigation as a final resort premised on the exhaustion of consensual mechanisms before judicial intervention. More critically, this study establishes that annual bonuses institutionalized through collective labor agreements constitute enforceable normative rights. An employer's unilateral internal memorandum that denies bonus entitlements to workers who completed active service throughout a fiscal year solely on the basis of administrative employment status at an arbitrary cut-off date constitutes unlawful discrimination under Article 6 of the Manpower Law. The PHI correctly applied a proportional accrual methodology, affirming that retirement does not extinguish rights vested through prior performance.